The Effect of Experience and Complexity of The Technology Acceptance Model (TAM) on Accepting Applications (E-PKH) In East Java - Galuh Andika; Ilyas Masudin; Fien Zulfikarijah (Business Innovation Management and Entrepreneurship Journal, 2022)
The purpose of this study is to examine and analyze the effect of experience and complexity of TAM on the EPKH application system used to report data at the Ministry of Social Affairs. This research is a quantitative study using data collection methods by distributing questionnaires to 150 respondents, namely social assistants in East Java. This type of research is explanatory research, the determination of the sample is done by the non-probability sampling technique and using a purposive sampling method. The collected data is then tested and analyzed using the Smart PLS program. The results showed that experience had no significant effect on perceived usefulness, while experience had a significant effect on perceived ease of use. Complexity also has a significant effect on perceived usefulness. Perceived ease of use has a significant effect on perceived usefulness, perceived usefulness has a significant effect on the intention to use and intention to use significantly affects real use.